Potensi Pemberdayaan Rumah Masyarakat Menjadi Homestay di Desa Pao Kecamatan Tombolopao Kabupaten Gowa Sulawesi Selatan - Ab, Ahmad; Hasbi, Andi; Poke, Andi Alif Rahmatullah; Alghazali, Muhammad Adam; Kuba, Dharma (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Potential Empowerment of Community Houses into Homestays in Pao Village, Tombolopao District, Gowa Regency, South Sulawesi Empowering community houses into homestays will increase the community's economic income. This community service activity aims to assist the community with the benefits that the community will feel if Pao Village becomes a tourist village. Another goal is to find out the potential of community houses for some of the rooms to be rented out as homestays. The method used is observation and interviews with homeowners whose houses have the potential to be used as homestays. The community houses that were observed were houses recommended by the village government that had potential. The results of this assistance show a positive and enthusiastic response from homeowners if their houses become homestays.